Penguatan Tata Kelola Pemilu Digital melalui Evaluasi Implementasi SIREKAP di KPU Provinsi Sulawesi Utara - Tangka, George; Longkutoy, Desmond; Mokodaser, Wilsen Grivin (Servitium Smart Journal, 2025)
The 2024 simultaneous elections relied on the Vote Recapitulation Information System (SIREKAP) to enhance transparency, but its implementation in North Sulawesi faced technical and non-technical challenges. This community service activity evaluated SIREKAP's implementation using the CIPP model (Context, Input, Process, Product) through in-depth interviews and FGDs with 30 election organizers. Key findings revealed three critical issues: (1) uneven internet infrastructure causing 40% of remote polling stations to fail in data uploads, (2) low digital literacy among 65% of polling officers (KPPS), and (3) only 85% accuracy of the OCR feature in reading C1 forms. Recommendations include simulation-based training, offline mode development, and open-source code audits. The study underscores the need for a holistic approach to digital election transformation, integrating technical, human resource, and infrastructure aspects